Memaknai Realitas Kemiskinan Kultural di Pedesaan: Sebuah Pendekatan Partisipatoris - Istato Hudayana; Nurhadi Nurhadi (Department of Social Development and Welfare, Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2020)
This article aims to reveal how the members of the poor family perceive wellbeing and poverty. This article is based on the theory of cultural poverty which sees the existence of a set of cultures that cause poor people difficult to escape from poverty. The research method used is qualitative inductive (exploratory) through phenomenology approach and data analysis uses descriptive analysis. The important finding of the study is that the poor perceived wellbeing as multiple and gradual i.e. (i) have healthy physical, (ii) a harmonic relation with others in communities and (iii) have enough money to meet the basic needs, especially, food. There is a dualistic view of poverty, between they accept as in the philosophy of